CONTINGENCY THEORY AS A DECISION-MAKING FUNDAMENTAL IN BUSINESS ANALYSIS - Pahlefy, Muhamad Reza; Putri, Tasya Amanda; Wenedy, Aaron (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
In the dynamic landscape of organizational decision-making, the effectiveness of frameworks like AIDA, STP, Porter's Five Forces, VRIO, and Ansoff Matrix often depends on situational variables, as highlighted by Contingency Theory. This study investigates the application of Contingency Theory in aligning decision-making and leadership strategies with specific contextual demands. Employing a literature review methodology, data was gathered from credible academic sources to analyze the theoretical underpinnings and practical applications of Contingency Theory in business analysis. Findings reveal that successful decision-making hinges on environmental scanning, strategic fit, and adaptability to dynamic conditions. Moreover, leadership styles guided by contingency principles, such as the Situational Leadership Model, demonstrate the importance of adapting to organizational and environmental complexities. This study underscores the critical role of contingency-based approaches in fostering organizational resilience and effectiveness, offering valuable implications for both practitioners and academics in navigating multifaceted business challenges.